Association Between Maternal Folic Acid Supplementation and Congenital Heart Defects in Offspring in Birth Cohorts From Denmark and Norway. Issue 6 (19th March 2019) - Øyen, Nina; Olsen, Sjurdur F.; Basit, Saima; Leirgul, Elisabeth; Strøm, Marin; Carstensen, Lisbeth; Granström, Charlotta; Tell, Grethe S.; Magnus, Per; Vollset, Stein E.; Wohlfahrt, Jan; Melbye, Mads
Abstract : Background: Evidence linking individual‐level maternal folic acid supplementation to offspring risk of congenital heart defects is lacking. We investigated whether folic acid supplementation in early pregnancy reduces offspring risk of heart defects in 2 large birth cohort studies. Methods and Results: Women recruited in early pregnancy within the DNBC (Danish National Birth Cohort), 1996–2003, and MoBa (Norwegian Mother and Child Cohort Study), 2000–2009, were followed until delivery. Information on periconceptional intake of folic acid and other supplements was linked with information on heart defects from national registers. Among 197 123 births, we identified 2247 individuals with heart defects (114/10 000). Periconceptional (4 weeks before through 8 weeks after conception) use of folic acid plus other supplements (54.8%), folic acid only (12.2%), and non–folic acid supplements (5.0%) were compared with no supplement use (28.0%); the adjusted relative risks of heart defects were 0.99 (95% CI, 0.80–1.22), 1.08 (95% CI, 0.93–1.25), and 1.07 (95% CI, 0.97–1.19), respectively. For initiation of folic acid in the preconception period weeks −4 to −1 (33.7%) and the postconception periods 0 to 4 weeks (15.5%), 5 to 8 weeks (17.8%), and 9 to 12 weeks (4.6%), compared with no or late folic acid intake (29.1%), relative risks of heart defect were 1.11 (95% CI, 1.00–1.25), 1.09 (95% CI, 0.95–1.25), 0.98 (95% CI, 0.86–1.12), and 0.97 (95% CI, 0.78–1.20), respectively. Relative risks of severe defects, conotruncal defects, and septal defects showed similar results. Conclusions: Folic acid was not associated with offspring risk of heart defects, including severe defects, conotruncal defects, or septal defects.